Isodon villosus (Nepetoideae, Lamiaceae), a new species from Guangxi, China - Chen, Ya-Ping; Xiang, Chun-Lei; Sunojkumar, Purayidathkandy; Peng, Hua (Phytotaxa, 2016)
Isodon villosus, a new species from Guangxi, southern China, is here described and illustrated. It is morphologically close to I. lophanthoides and I. phyllopodus, but differs from the former by its declinate corolla tube, included stamens and style, and larger mericarp, and from the latter by its base of lamina not decurrent on petiole, panicle densely septate-villose, as well as posterior lip without spot. A key to all 15 taxa of Isodon from Guangxi is also provided.